(untitled) (Journal of Laboratory Animal Science, 2024)
The laboratory zebrafish (Danio rerio) is a well-established vertebrate animal model in frontline areas of modern biology research, including screening of therapeutic molecules and assessment of toxic chemicals. High fecundity is one of the important reproductive traits in zebrafish females that benefit researchers in obtaining a large number of embryos for high throughput experiments. External fertilization offers easy access to the embryos up to 5 days post fertilization without ethical concerns whilst optical transparency of developing embryos allows for imaging of the entire embryo, which is not practical in mammalian models. Despite being prolific breeders, laboratory zebrafish exhibit a reduction in reproductive performance aftertwo years. In vitro fertilization, which uses frozen sperm, is an effective method for reviving genetically modified fish lines. In this study, we attempted to us e an IVF approach to re store zebrafish lines from aged zebrafish. A total of 12 zebrafish lines were reproduced using the IVF procedure, including aged fish that are unable to spawn naturally. A total of 974 (66.96%) and 1438 (55.67%) embryos survived utilizing the IVF procedure with germ cells from both mutant and wild-type parents, respectively. Zebrafish embryos survived at a rate of 67.34% in the 2–3-years age groupand55.48% in the 3-4 years age group.